2021
DOI: 10.1186/s12935-021-01991-z
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle transporter GOLT1B mediates the cell membrane localization of DVL2 and PD-L2 and promotes colorectal cancer metastasis

Abstract: Background Colorectal cancer (CRC) is the third most diagnosed and second leading cause of cancer death worldwide. Hallmark proteins processing is usually dysregulated in cancers. Finding key regulatory molecules is of great importance for CRC metastasis intervention. GOLT1B is a vesicle transport protein which is involved in cytosolic proteins trafficking. However, its role in cancer has never been addressed. Methods CRC cell lines and subcutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 51 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…Besides, high expression of GOLT1B suggests poor prognosis of colorectal cancer, and induces immunosuppression by promoting PD-L2 membrane localization (7). Consistent with the previous report, our study revealed that the expression of GOLT1B was higher in breast cancer tissues than normal tissues (Figure 1).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Besides, high expression of GOLT1B suggests poor prognosis of colorectal cancer, and induces immunosuppression by promoting PD-L2 membrane localization (7). Consistent with the previous report, our study revealed that the expression of GOLT1B was higher in breast cancer tissues than normal tissues (Figure 1).…”
Section: Discussionsupporting
confidence: 91%
“…One current study has uncovered that the overexpression of GOLT1B can elevate the cell membrane level of DVL2, then activate Wnt/bcatenin pathway, increase the content of nuclear b-catenin, and subsequently induce the process named epithelial-mesenchymal transformation. On the other hand, GOLT1B also promotes the migration and invasion of colorectal cancer via inducing T lymphocyte apoptosis (7). Poorer prognosis has been observed in patients with GOLT1B amplifications in lung adenocarcinoma (8).…”
Section: Introductionmentioning
confidence: 99%
“…GOLT1B is a vesicle transport protein involved in cytoplasmic protein transport. Overexpression of GOLT1B can increase the level of DVL2 and enhance its plasma membrane translocation, then activate the downstream Wnt/β-catenin pathway and increase the level of nuclear β-catenin, thereby inducing epithelial-mesenchymal transition (EMT) [ 112 ]. DCZ0415, a small molecule inhibitor against TRIP13, inhibits EMT and metastasis in colorectal cancer by inactivating the FGFR4/STAT3 axis and the Wnt/β-catenin pathway [ 113 ].…”
Section: Wnt Pathway-related Biochemical Processmentioning
confidence: 99%
“…Others GOLT1B. Golgi transport 1 B (GOLT1B) as a vesicle transporter that participates in protein trafficking in cytoplasm increases PD-L2 expression and facilitates PD-L2 membrane localization in colorectal cancer to promote apoptosis of T cells and decreases IFN-γ expression, which in turn promotes migration and invasion in CRC [30]. MMP9/13.…”
Section: Post-translational Regulationmentioning
confidence: 99%